Environmental Impacts of Battery Recycling (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The production of rechargeable batteries, particularly lithium-ion batteries, can have significant environmental impacts. These are recycled by grinding them, neutralizing the acid, and separating the polymers from the lead. The recovered materials are used in a variety of applications, including new batteries. The lead in a lead–acid battery can be recycled. These include the environmental cost of mining lithium and other materials, the energy-intensive production process, and the challenges associated with recycling. Recycling provides many benefits to our environment. By recycling our materials, we create a healthier planet for ourselves and future generations. Conserve natural resources: Recycling reduces the need to extract resources such as timber, water, and minerals for new products. This article will primarily describes the impact of battery recycling and the benefits of battery recycling.